Pengaruh Social Media Marketing Terhadap Electronic Word of Mouth Pelanggan Gojek di Kota Surabaya yang dimediasi Consumer Engagement - Hardono, Irfan (Seminar Nasional Ilmu Terapan, 2024)
The increasingly rapid development of the digital era from time to time is also supported by the presence of increasingly sophisticated technology increasing the mobility of social media use, including in the field of online transportation services. This research aims to examine the influence of social media marketing on electronic word of mouth of Gojek consumers in Surabaya which is mediated by consumer engagement. The research method used is quantitative. The population in this study was the population of Bulak Village, totaling 21,529 residents. Meanwhile, the sample is the population of Bulak Subdistrict, totaling 21,529 residents, who have used Gojek transportation services. The research variables consist of the independent variable: social media marketing (X), the dependent variable: electronic word of mouth (Y) and the mediator variable: consumer engagement (Z). The data analysis technique uses multivariate statistical techniques. The research results show that social media marketing has a significant effect on the electronic word of mouth of Gojek customers in Bulak sub-district in Surabaya City. This proves that the higher the social media marketing, the higher the electronic word of mouth of consumers. Consumer engagement mediates the influence of social media marketing on electronic word of mouth of Gojek customers in Bulak Village in Surabaya City. This proves that the higher the social media marketing, the higher the electronic word of mouth of consumers through consumer engagement.